Process of Minang’s Women Migration in Jakarta - Oktavi, Sinta; Sumarti, Titik (Departement of Communication and Community Development Sciences, Faculty of Human Ecology, 2015)
T h e p u rpo ses o f th is s tu d y we re to a n a lyze th e m ig ra tio n p ro cess o f M in a n g ’s wo m en . T h e stu d y sh o w th a t (1 ) sin ce 1 9 80 M ina ng ’s wo m en ten d to m igra te in d irect wa y to th e d est in a tio n a rea wh i ch th ey h a ve ch o o se a nd in th e ca se o f M in an g ’s wo m en in Ja ka rta it’s m ea n th a t th ey wen t to Ja ka rt a d irectly, wh il e transit trend in the other destination area seldom practiced. The trend of direct migration pattern to Jakarta also supported by the improvement of the transportations facilities. Along with it, women migration flo w b e co m es m o re o p en sin ce th e M in a n g ’s wo m en m ig ra tio n wa s ch a in m ig ra tio n ba sed o n kin sh ip wh o have migrate first (2)Although Minang women migrant have stay in destination area for 5 (five) years or more, they keep coming back to their origin area even once in a while. K ey wo rd s: M in a n g ’s wo m en m ig ra n ts, pa tter n an d flo w o f m ig ra tion